The structural behaviour of laminated-guadua panels under parallel plane loads (2012)
The Universidad Nacional de Colombia "Analysis, Design and Materials - GIES" research group tested two types of panels made from Guadua angustifolia Kunth and poly vinyl acetate (PVA) as a first step in studying the behaviour of laminated guadua frames having panels of the same material under seismic load: type 1 panels had a solid cross-section and type 2 panels a sandwich cross-section.Each type of panel had three different heights and 10 replicates were tested for each type and height (60 trials in total).Each panel’s load compared to displacement curve was found; 0.34m and 0.63m type1 panels had initial elastic behaviour followed by inelastic behaviour while 0.98 m panels made of both types had an almost completely elastic behaviour until failure. All panels became crushed at their base; however, the main failure mechanism was warping.